A dynamic approach for evaluating the moment rigidity and rotation precision of a bearing-planetary frame rotor system used in RV reducer. (July 2022) - Xie, Yun Hong; Xu, Li Xin; Deng, Yun Qing
Highlights: A dynamic model is proposed for the bearing rotor system in RV reducer. Method for calculating balls-races contact deflection is optimized. Effects of different factors on moment rigidity and rotation precision are analyzed. Dynamic characteristics of the reducer center spatial rotation trajectory are obtained. Abstract: The rotating vector reducer (RV reducer) is widely used in joint transmission of industrial robots. The moment rigidity and rotation precision of the non-standard angular contact ball bearings-planetary frame rotor system (BPFRS) in the RV reducer have a significant impact on the service performance of industrial robots. This paper presents an improved dynamic model to study the moment rigidity and rotation precision of the BPFRS. The proposed model optimizes the theoretical method for calculating balls-races contact deflection and contact angle, which can more precisely describe the locus of the inner race groove curvature center. Furthermore, a moment rigidity test experiment is designed to verify the accuracy of the proposed model. On the basis, effects of different load conditions, axial preload displacement, numbers of balls, and combinations of inner and outer race groove curvature radius coefficients on moment rigidity and rotation precision of the BPFRS are analyzed, respectively. The results show that these factors have a significant effect on moment rigidity and rotation precision. Besides, dynamic characteristics of the spatial rotation trajectory of the reducer center are obtained.